Teaching the block of private law disciplines in the master’s degree: new challenges in the conditions of the reform of legal education and distance learning - Zozuliak, Olha; Bashuryn, Nataliia (Actual problems of law (Aktual’ni problemi pravoznavstva), 2023)
The article is devoted to the theoretical-applied analysis of the key aspects of the application of the latest methods of teaching the block of private law disciplines in the master’s degree in the conditions of the reform of legal education and distance learning in Ukraine. The authors of the article emphasize the need to combine three main components when teaching private law disciplines: 1) characteristics of modern civil legislation; 2) studying the doctrine of civil law; 3) practices of its application. It is pointed out the need to apply the positive experience of the leading EU countries when teaching sectoral legal disciplines; the need for an in-depth analysis of the practice of the European Court of Human Rights; characteristics of civil law institutions in the context of comparative jurisprudence. It is pointed out that classes should be fundamentally problem-based with systematic analysis and analysis of scientific publications. Emphasis is placed on the unique importance of involving students in scientific circles of a civic orientation, participation in conferences and other events of a scientific and practical nature. The prospects of strengthening the practical component during the training of future lawyers through the involvement of practicing lawyers in the educational process were analyzed in detail; changing approaches to the internship process and student practice; reforming the activity of legal clinics with the aim of forming professional competences of the future lawyer in accordance with the Law of Ukraine "On Higher Education". Investigating the issues of distance education in obtaining a legal education, the authors emphasize the relevance of measures taken in the educational process during air raids in wartime conditions and state the perspective of the mixed form of education as a format for the training of future lawyers, which allows to adapt to various unstable and ambiguous conditions, including in the conditions of martial law in Ukraine.